(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
Metabolic syndrome (MetS) is a highly prevalent complex disorder among adults worldwide which includes cardiovascular risk factors such as central obesity, insulin resistance, dyslipidemia and hypertension. MetS or its components are prevalent in patients with benign prostate hyperplasia (BPH), a common urogenital disorder of adult male with increasing age. This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2014 to June 2015 with a total of 100 subjects. Of these 50 patients of BPH attending the Department of Urology, Dhaka Medical College Hospital, Dhaka was taken as Group I and 50 age-matched apparently healthy adults was taken as Group II. According to the National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP III, 2005) criteria, components of MetS as fasting plasma glucose, serum triglyceride, serum HDL-C level, blood pressure, waist circumference were assessed and compared between groups by chi-square (x2) tests and unpaired student’s ’t’ test as appropriate. A p value <0.05 at 95% CI was considered as significant. Metabolic Syndrome was significantly more common in BPH patients than that of healthy individuals (72% VS 38%, p=0.001). Mean±SD of fasting plasma glucose and serum triglycerides were significantly higher in Group I than that of Group II (5.7±0.6 mmol/l vs 5.13±0.97 mmol/l, p=0.001; and 191.3±33.9 mg/dl vs 159.2±45.5 mg/dl, p=0.001, respectively). Percentage of subjects having high blood pressure, high serum triglyceride and low serum HDL-C were significantly high in BPH patients (Group I) than that of healthy individuals of Group II (BP: 72% VS 44%, p=0.005, TG: 90% vs 54%, p=0.001, HDL-C: 72% VS 54%,p=0.001). Metabolic syndrome or its components are more common among patients with benign prostate hyperplasia. Routine investigations to detect MetS can be done to reduce the risk of cerebrovascular diseases, cardiovascular diseases and type 2 diabetes mellitus in BPH patients. Bangladesh J Med Biochem 2015; 8(2): 42-48